2015
DOI: 10.1210/en.2015-1333
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Supresses Sympathetic Hyperexcitation in Acute Heart Failure in Male Rats: Assessing Centrally and Peripherally Mediated Pathways

Abstract: The hormone ghrelin prevents a dangerous increase in cardiac sympathetic nerve activity (SNA) after acute myocardial infarction (MI), although the underlying mechanisms remain unknown. This study aimed to determine whether ghrelin's sympathoinhibitory properties stem either from directly within the central nervous system, or via modulation of specific cardiac vagal inhibitory afferents. Cardiac SNA was recorded in urethane-anesthetized rats for 3 hours after the ligation of the left anterior descending coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…The apparent lack of an effect of the b-AR blockade on the coronary circulation of ghrelin-treated animals is likely linked to the sympathoinhibitory properties of ghrelin, as we have consistently confirmed that ghrelin effectively prevents adverse sympathetic activation following acute MI (5)(6)(7)40). It is plausible, therefore, that the effect of the b-AR blockade in ghrelin-treated MI animals was negligible, as the b-ARs were not activated in the first place.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…The apparent lack of an effect of the b-AR blockade on the coronary circulation of ghrelin-treated animals is likely linked to the sympathoinhibitory properties of ghrelin, as we have consistently confirmed that ghrelin effectively prevents adverse sympathetic activation following acute MI (5)(6)(7)40). It is plausible, therefore, that the effect of the b-AR blockade in ghrelin-treated MI animals was negligible, as the b-ARs were not activated in the first place.…”
Section: Discussionsupporting
confidence: 51%
“…However, all of the measured parameters of cardiac work (HR, LVESP, contractility, and ABP) for sham rats in this study were unaltered by ghrelin. Moreover, we have consistently reported that modulation of SNA by ghrelin is not evident in sham animals, rather only in those animals with an MI where SNA adversely increases (6,7,27).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The functional preservation of Cx43 by eliciting CAP would play an irreplaceable role in antiarrhythmogenic properties during ICM. Interestingly, Shirai et al 40 reported that bilateral vagotomy attenuated the cardiac sympathetic nerve activity response to acute MI that, in turn, reduced the incidence of arrhythmic episodes. In contrast, our study suggested that unilateral vagotomy not only aggravated the abnormality of ICM rats and increased the inducibility quotient of ventricular arrhythmias but also attenuated the effects of eliciting CAP.…”
Section: Discussionmentioning
confidence: 99%